Seksualitas Manusia di Era Digital: Terbentuknya Budaya Cybersex dalam Komunitas Siber - Musarrofa, Ita; Sa’adah, Mazro’atus (The Sociology of Islam, 2024)
The digital era allows sexual activities to be carried out online. This article aims to look at cybersex culture and how the reality of that culture is formed. Data about cybersex was extracted from previous research and sites on the internet that describe the reality of cybersex. This data was then analyzed using content analysis. The theories used are Peter L. Berger's dialectical theory of externalization, objectivation and internalization and the uses and gratification theory. This research found that the formation of sexual culture in the digital era comes from externalization, both by consumers and producers of cybersex. Externalization by producers takes the form of providing pornographic sites, pornographic videos and images, and long-distance sex equipment. The continued interest in cybersex makes manufacturers continue to produce sex services and develop online sex equipment. Cybersex becomes a compelling objective reality that must be internalized in cybersociety’s subjective consciousness and influence the next externalization stage. Cybersex has become a medium for channelling sexual needs because it is considered safe from various social risks, cheap and practical.